2017
DOI: 10.1002/oca.2390
|View full text |Cite
|
Sign up to set email alerts
|

The optimal control of Axelrod's social norm game

Abstract: Summary In this paper, we study the well‐known Axelrod's social norm game using replicator dynamics and control theory. In general, a social norm game has 4 pure strategies: norm following and norm defecting, each of which branching further into punishing or not punishing others for defection, if observed. Our aim is to check whether by introducing a control parameter that mimics incentives for players who follow the norm, we observe changes in the dynamics of the strategy game, which maximize norm‐following s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…A numerical method to solve this problem is the steepest descent (SD) method whose algorithm is presented in (Kirk, 2012) and (Wang, 2009). We used this method in similar work to solve an optimal control of a social norm game in (Jaber & Cojocaru, 2018) and to solve the optimal control of a preventive treatment game in (Cojocaru & Jaber, 2018) to maximize the number of players who choose to vaccinate in an epidemiological model.…”
Section: Optimal Control Of Infectious Populationsmentioning
confidence: 99%
“…A numerical method to solve this problem is the steepest descent (SD) method whose algorithm is presented in (Kirk, 2012) and (Wang, 2009). We used this method in similar work to solve an optimal control of a social norm game in (Jaber & Cojocaru, 2018) and to solve the optimal control of a preventive treatment game in (Cojocaru & Jaber, 2018) to maximize the number of players who choose to vaccinate in an epidemiological model.…”
Section: Optimal Control Of Infectious Populationsmentioning
confidence: 99%
“…In [28] built a novel model to optimize cancer chemotherapy by studying it as an evolutionary game between cancer and the oncologist. In our most recent work, we applied optimal control to a replicator dynamics system of a norms game in a population, and we showed that the otherwise evolutionarily stable state of all defectors can be controlled towards a norm-dominated population [29].…”
Section: One Of the Common Ways To Analyze This Issue Ismentioning
confidence: 99%
“…Moreover, we are going to follow the same formulation as in [29] to build up a classical optimal control problem where we want to minimize the following functional problem:…”
Section: Optimal Control Of Vaccination Away From the Nash-pareto Statementioning
confidence: 99%
See 1 more Smart Citation